Phylogenetic analysis of Streptomyces producing antimicrobial agent isolated from Kukup Beach Sand, Yogyakarta, Indonesia - AMBARWATI AMBARWATI; BROTO SANTOSO; AAN SOFYAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ambarwati A, Santoso B, Sofyan A. 2023. Phylogenetic analysis of Streptomyces producing antimicrobial agent isolated from Kukup Beach Sand, Yogyakarta, Indonesia. Biodiversitas 24: 2374-2383. Microorganisms such as bacteria, fungi, and Streptomyces are sources of bioactive compounds. Streptomyces is known as the largest antibiotic-producing genus. This study aimed to determine the antimicrobial activity of Streptomyces isolates and analyze the relationship between Streptomyces isolates based on the 16S rRNA gene sequence. The Streptomyces isolates were screened for their antimicrobial activity based on their ability to inhibit test bacteria growth using the agar block method. The selected isolates that showed antimicrobial activity were molecularly characterized using 16S rRNA gene sequence analysis. The result showed 32 Streptomyces isolates successfully isolated on SCA and Raffinosa Histidine Agar media. Among 32 isolates, it was observed that five isolates demonstrated the ability to inhibit the test bacteria growth on 9 to 25 mm of inhibition zone diameters. The BRI-18 isolate showed the highest antimicrobial activity inhibiting Bacillus subtilis G. FNCC 0060 on 25 mm of inhibition zone diameter (strong inhibition category). Based on 16S rRNA sequences, it was known that five isolates belonged to Streptomyces. BLAST analysis on the ARA-5 isolate revealed that it was closely related to Streptomyces griseoincarnatus strain JCM 4381 with 99.62% sequence similarities. The AR3-29 isolate was a sister clade identical to Streptomyces rochei strain NRRL B-1559 with a 99.35% similarity level. The BRI-18 and BRI-19 isolates were the most similar to Streptomyces fradiae strain NBRC 12773 on 96.87% and 95.15% index similarity, respectively, whereas the BRI-35 isolate demonstrated the highest similarity to Streptomyces zhihengii strain YIM T102 (97.02%). The research demonstrated that Streptomyces isolates from Kukup beach sand showed the potential as an antimicrobial agent.